Gondwanan perspectives: cretaceous-paleogene biota of west Antarctica - Reguero, Marcelo Alfredo; Olivero, Eduardo Bernardo; Pol, Diego
Antarctica has played a key role connecting all major land-masses of Gondwana, even during periods of their break up through the Cretaceous and Paleogene. The largely ice-covered rocks of Antarctica undoubtedly contain countless clues about the paleogeographic and biotic connections of southern Gondwana. The Antarctic Peninsula is the region that has provided and that likely will provide the most informative fossil remains from the Cretaceous–Paleogene. In particular, during the past two decades, geologic and paleontological explorations of the James Ross Basin, Weddell Sea, have revealed that this basin, located off the northeast tip of the Antarctic Peninsula (West Antarctica), contains one of the most important records of Late Cretaceous and early Paleogene life in the Southern Hemisphere. Fil: Reguero, Marcelo Alfredo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Pol, Diego. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina